2019
DOI: 10.1371/journal.pone.0205633
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the iDSI reference case among published cost-per-DALY averted studies

Abstract: Background The iDSI reference case, originally published in 2014, aims to improve the quality and comparability of cost-effectiveness analyses (CEA). This study assesses whether the development of the guideline is associated with an improvement in methodological and reporting practices for CEAs using disability-adjusted life-years (DALYs). Methods We analyzed the Tufts Medical Center Global Health CEA Registry to identify cost-per-DALY averted studies published from 201… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Third, we excluded other methods of examining equity effects in CEAs (eg, MCDA), which can also be used to ensure that equity is considered in decision making. Finally, although 64% of included studies met the complete CHEERS checklist, which is within the range that previous systematic reviews on other topics have reported, [96][97][98] the checklist itself does not evaluate the quality of CEAs and only how they are reported. 99…”
Section: Discussionmentioning
confidence: 65%
“…Third, we excluded other methods of examining equity effects in CEAs (eg, MCDA), which can also be used to ensure that equity is considered in decision making. Finally, although 64% of included studies met the complete CHEERS checklist, which is within the range that previous systematic reviews on other topics have reported, [96][97][98] the checklist itself does not evaluate the quality of CEAs and only how they are reported. 99…”
Section: Discussionmentioning
confidence: 65%
“…This framework is in development and will be based on similar initiatives internationally. 22 The populations of interest are average-risk Australians and subgroups relevant to the modelled evaluations. For each evaluation, several primary outcomes are considered, including the following: ► Health benefits, for example, reduction in lifetime risk of CRC incidence and mortality.…”
Section: Policy1-bowel Validationmentioning
confidence: 99%
“…In this way, the iDSI reference case aimed to achieve broad applicability but local relevance to decision maker's needs. A recent review [4] of the formal take-up of the iDSI reference case in journal publications reporting cost per disability-adjusted life year found limited explicit citation of the iDSI reference case; however, this may reflect the iDSI focus on the direct policy process and supporting analytics, much of which may not achieve publication. It also demonstrates that quality improvement initiatives require dedicated action to encourage uptake from decision makers, who, in the case of global health are often-times development partners and are not always the same as the beneficiaries of improved decisions, which such methodological standards as the reference case are supposed to inform.…”
Section: The International Decision Support Initiative Reference Casementioning
confidence: 99%